Globalization and disease: in an unequal world, unequal health! - Paulo Marchiori Buss
In this paper, originally presented at an event held by the National Institutes of Health (NIH) in the United States, the author analyzes the repercussions of globalization on various health aspects: the spread of infectious and parasitic diseases, bioterrorism, and new behavioral patterns in health, among others. He goes on to examine the positive and negative effects of international agreements on health, particularly in the trade area, including the TRIPS Agreement on medicines in the area of public health. The paper concludes that the resumption of cooperation among nations is the best way to achieve world progress in public health.